Relationship between caloric intake and energy expenditure among schoolchildren in both sexes aged 07 to 10 years of elementary school in a public school in the municipality of Cacoal - RO - Romanholo, Rafael Ayres (2012)
The inactivity and poor nutrition in childhood and adolescence are contributing to the increase of obesity in this and in subsequent age groups, especially in populations with low purchasing power. The general objective of the research was linked to caloric intake, energy expenditure and scholars of both sexes, aged between 07 and 10 years of basic education in a public school in the municipality of Cacoal - RO. To carry out the search the sample with the participation of 100 schoolchildren who were randomly defined and the sample for convenience, aged between 07 and 10 years enrolled in schools in a network of public education municipal chosen. As the body mass of girls and boys, was studied been a significant interaction between the caloric intake of age and sex (p <0.0001), and also with the progression of age showed that the figures were increasing, 7, 8.9 and 10 years of age on the pattern of NCHS, for girls and for boys the same age. The relationship between the average calorie intake and expenditure of children assessed, where the average caloric intake for women stood at 2119.6 and standard deviation of 511.9 and the boys stood at 2238.1 and standard deviation of 570. In this study was concluded that children eat more calories than spend, showing that it is essential to educate the adoption of healthy habits, since childhood.